Мишка-воришка - Гурина Ирина Валерьевна (Начинаем читать сами, 2016)
Экземпляры: ф16 (20171115) / Инвентарный номер: 55034 / Цена: 13.00 / Сис.шифр: Д / Авт.знак: Г 95 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6